Acute tubulointerstitial nephritis associated with atezolizumab, an anti-programmed death-ligand 1 (pd-l1) antibody therapy. (3rd July 2018) - Xipell, M.; Victoria, I.; Hoffmann, V.; Villarreal, J.; García-Herrera, A.; Reig, O.; Rodas, L.; Blasco, M.; Poch, E.; Mellado, B.; Quintana, L. F.
ABSTRACT: Direct stimulation of the antitumor activity of immune system through checkpoint inhibitors (ICIs) has demonstrated efficacy in the treatment of different cancer types. The activity of these antibodies takes place in the immunological synapse blocking the binding of the negative immunoregulatory proteins, thus leading to the finalization of the immune response. Despite having a favorable toxicity profile, its mechanism of action impedes the negative regulation of the immune activity which can potentially favor autoimmune attacks to normal tissues. Renal toxicity has been described in several ICI but not with atezolizumab, an IgG1 monoclonal antibody targeting PD-L1 (programmed death ligand 1), approved by FDA as a second-line therapy for advanced urothelial carcinoma. Here we present a patient with a single kidney and metastatic renal cell carcinoma treated with atezolizumab and bevacizumab combination, with biopsy-proven acute interstitial nephritis, who had a complete resolution of renal dysfunction after steroid therapy.